Detecting Cosmic Rays with the Murchison Widefield Array - Williamson, Alexander (Curtin University, 2021)
The study of cosmic rays provides a rare view of the nature of the universe. The remote environment and flexibility of the Murchison Widefield Array make this radio telescope ideal for the intricate task of studying these cosmic rays. The research presented in this thesis has proved this to be achievable with a sensitivity and precision matched by few other instruments around the world.